The role of infrared thermography (IRT) and magnetic resonance imaging (MRI) in brown fat evaluation and their application to study the effect of thyroid status on brown fat activity and white fat partitioning - Leow, Melvin Khee Shing (Nanyang Technological University, 2020)
My proposed research falls under the field of Metabolic Physiology. Metabolism, being the sum total of all anabolic and catabolic activities of cells and organs determine the net energy balance of all vertebrates. The complex metabolic networks that fuel life itself are functionally a downstream effector layer governed by regulatory feedback loops including those constituting a part of the endocrine system. Among the wide range of hormones controlling intermediary metabolism such as insulin, glucagon, cortisol and catecholamines, the homeostatic equilibrium established by thyroid hormones appear to be a key driver of metabolic rate which influences the boundary between health and disease. Recent work revealed that the potent thermogenic effect of thyroid hormones is mediated by brown adipose tissue (BAT). Dissecting the physiological mechanisms and metabolic pathways of this process is a very active field of investigation that is interdisciplinary in nature and requires a variety of approaches. Research in this field of metabolic physiology has allowed me to explore and interrogate the effect of thyroid status on brown fat thermogenesis, metabolic rate, fat distribution, body composition and weight control. The clinical significance of deciphering the relationship between thyroid status, brown fat activation and the browning of white fat lies in unravelling the possibility for optimisation of health and quality of life of numerous thyroid patients and offering insights in augmenting energy expenditure as a strategy to counter the present epidemic of obesity and diabetes confronting the world. An overarching goal is that of developing and validating infrared thermography (IRT) that incorporates a novel image processing algorithm for heat power efflux quantification and also establishing fat fraction MRI for precise brown fat volumetric measurement to address my hypotheses and facilitate studies of brown fat. The quest to better understand the inter-relationships above essentially form much of my research work and endeavor that is detailed in the pages of this PhD thesis.